Relationship Between Hemoglobin Levels (Hb) and Nutritional Status with Academic Achievements of STIK KESOSI TLM Students in 2022 - Nofri Eka Yuliandi; Apriani Apriani; Laili Safitri; Aris Cristian Manulang (Nusantara Scientific Medical, 2022)
Students who excellence academically are always associated with good health status. One indicator of health status that is commonly used is hemoglobin (Hb) and nutritional status. Hb levels can be an indicator of anemia and nutritional status can be a measure of a person's brain development ability. The purpose of this study was to determine the relationship between hemoglobin (Hb) levels and nutritional status with the academic achievement of TLM STIK KESOSI students in 2022. The research design was cross-sectional, and sampling was carried out in October - November 2022. Sampling using a non-random technique, with a total sample of as many as 36 students. Data collection was carried out by measuring Hb levels, body weight, and height. The data obtained were analyzed by univariate and bivariate. The results showed that 47.2% of students were in the category of normal nutritional status, and 91.7% were not anemia. The relationship between Hb levels and student nutritional status on student academic achievement showed no significant relationship (P> 0.05). In conclusion, normal or not Hb levels and nutritional status did not affect student learning achievement. However, efforts are still needed to maintain the stability of Hb levels and nutritional status in students. So that the impact is not only to increase academic achievement but also to maintain the quality of long-term health.